Światło jako symbol mądrości i Prawa w Księdze Mądrości - Zieliński, Marcin (Verbum Vitae, 2016)
In the present article, the author analyzes the meaning and symbolic sense of light in the Book of Wisdom. The Wisdom in Wis 7:10 is interpreted not as superior to light but rather as a light which is a guide for the sage and a symbol of the wisdom of God. In pursuit of a deeper comprehension of this text, the author points to Wis 18,1-4 as important in developing the sense of light, and in particular the strong connection between light and the Jewish Law–the supreme light of wisdom that God gave to all the nations. The central position of these verses within the unit of Wis 16–19 points out the absolute importance of the Law, which is described as a true light. At the same time, the writer of the Book of Wisdom emphasizes the importance of the Law as imperishable and unchangeable, a cornerstone of religious life.